2015
DOI: 10.1371/journal.pone.0126992
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Host Gene Expression in Chicken Embryo Fibroblasts Infected with Reticuloendotheliosis Virus Strain HA1101

Abstract: Reticuloendotheliosis virus (REV), a member of the Gammaretrovirus genus in the Retroviridae family, causes an immunosuppressive, oncogenic and runting-stunting syndrome in multiple avian hosts. To better understand the host interactions at the transcriptional level, microarray data analysis was performed in chicken embryo fibroblast cells at 1, 3, 5, and 7 days after infection with REV. This study identified 1,785 differentially expressed genes that were classified into several functional groups including sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
0
10
0
1
Order By: Relevance
“…Previously, we have identified miRNAs expression profile of bursa of Fabricius in SPF chickens in response to REV infections and discovered that miRNAs not only involved in the up-regulation of genes related to proapoptotic, proto-oncogene, and carcinogenic cytokines, but also involved in down-regulation of genes related to anti-apoptotic cytokines (Yu et al, 2017 ). By using microarray analysis, Ji Miao analyzed the transcripotme of CEF and found that genes involved in immune response played important roles in the pathogenicity of REV infection (Ji et al, 2015 ). Here we identified five significantly over-expressed oncogenes including HRAS, B-Raf, c-myc, c-fos, and c-jun.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have identified miRNAs expression profile of bursa of Fabricius in SPF chickens in response to REV infections and discovered that miRNAs not only involved in the up-regulation of genes related to proapoptotic, proto-oncogene, and carcinogenic cytokines, but also involved in down-regulation of genes related to anti-apoptotic cytokines (Yu et al, 2017 ). By using microarray analysis, Ji Miao analyzed the transcripotme of CEF and found that genes involved in immune response played important roles in the pathogenicity of REV infection (Ji et al, 2015 ). Here we identified five significantly over-expressed oncogenes including HRAS, B-Raf, c-myc, c-fos, and c-jun.…”
Section: Discussionmentioning
confidence: 99%
“…In chickens, immune organs such as thymuses, spleens, and bursas are the sites where T- and B-cells differentiate. REV is known to attack the reticuloendothelial cells or lymphocytes to induce humoral and cellular immune suppression, inducing the abnormal development of immune organs and finally inducing immunosuppression of the host ( 3 , 15 ). In the current study, REV infection caused atrophy of thymuses and bursas, indicating the impaired immune function.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on chicken embryo fibroblast (CEF) cultures infected with reticuloendotheliosis virus HA1101 strain, differential expression of a number of genes leading to changes in several signalling pathways was reported [ 31 ]. We and others have shown upregulation of miR-155 in Rev-T-transformed cell lines and CEFs [ 32, 33 ].…”
Section: Introductionmentioning
confidence: 99%